2016
DOI: 10.1002/job.2109
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐break activities at work to recover from daily work demands

Abstract: SummaryRecovery literature has focused predominantly on recovery processes outside the workplace during nonwork times. Considering a lack of research on momentary recovery at work, we examined four categories of microbreak activities-relaxation, nutrition-intake, social, and cognitive activities-as possible recovery mechanisms in the workplace. Using effort recovery and conservation of resources theories, we hypothesized that micro-break activities attenuate the common stressor-strain relationship between work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
180
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(191 citation statements)
references
References 53 publications
5
180
1
5
Order By: Relevance
“…Furthermore, Study 2 revealed that downtime relates to outcomes of personal importance, namely, The result showing that employees who engaged in a higher percentage of relaxation activities during longer downtime periods reported lower fatigue levels warrants additional attention. Interestingly, this result is similar to most findings in the work breaks literature that show relaxing or microbreak activities are most beneficial to employee well-being (Kim et al, 2017;Strongman & Burt, 2000). It also is consistent with one recent paper that suggests being able to engage in leisure activities during downtime mitigates the negative effect of anticipating downtime (Brodsky & Amabile, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, Study 2 revealed that downtime relates to outcomes of personal importance, namely, The result showing that employees who engaged in a higher percentage of relaxation activities during longer downtime periods reported lower fatigue levels warrants additional attention. Interestingly, this result is similar to most findings in the work breaks literature that show relaxing or microbreak activities are most beneficial to employee well-being (Kim et al, 2017;Strongman & Burt, 2000). It also is consistent with one recent paper that suggests being able to engage in leisure activities during downtime mitigates the negative effect of anticipating downtime (Brodsky & Amabile, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…As fatigue and vitality fluctuate across a day, time of day is a common control variable in many ESM studies (e.g.,Kim et al, 2017). Whether the employees had breaks or not may be another confounder with downtime, and we also want to see the different effects of these two periods.…”
mentioning
confidence: 99%
“…Additionally, interventions could be aimed to increase job crafting, in which employees are encouraged to proactively optimize their own work environment (bottom‐up approach; Tims, Bakker, & Derks, ). For example, employees could try to increase social resources (e.g., seeking social support from their supervisor) or structural job resources (e.g., taking a self‐initiated short break from work if possible, or engaging in activities promoting recovery when a break can be taken; Kim, Park, & Niu, ; Kühnel et al, ). Workers could seek more challenging job demands (e.g., devoting time and effort to take care of patients' needs, in addition to delivering high‐quality care), which are positively associated with work engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Based on cross‐sectional survey data, Siltaloppi, Kinnunen, and Feldt () found that time demands possessed a positive and job control possessed a negative association with the need for resource recovery and job exhaustion, respectively. Kim, Park, and Niu's () longitudinal study indicated that relaxation breaks decreased work demands' negative impact on end‐of‐workday job strain. In another longitudinal study, Sianoja, Kinnunen, de Bloom, and Geurts () found that successful lunchtime recovery was negatively related to emotional exhaustion at work.…”
Section: Introductionmentioning
confidence: 99%